“Desarrollo de una aplicación móvil con administración web para la gestión de la producción lechera de ganado bovino de la hacienda Mayrita ubicada en el cantón Mejía” - Caiza Quinatoa, Martha Cecilia (2021)
The present technological proposal, allows to write the development process of a mobile system with web administration for the management of the dairy production of the Mayrita farm, located in the San Roque neighborhood, parish of Aloasi, canton Mejia, province of Pichincha. The farm carries out several activities, one of them is milk production, which generates a major economy. In which several difficulties were identified; manual registration of animals, manual milk production, no control of vaccines, no registration of workers, causing loss of documents, delay in finding some information, use of office materials without clear objectives, which results in not knowing the real state of the data of the farm. Because of this, the development of software to systematize the control and registration of the dairy production of cattle using free software tools is proposed. For the development of the project, research methodologies were used, framed in the type of research; descriptive, field, bibliographic, data collection techniques and instruments; interviews, survey, observation, in order to understand the problem and identify the main needs. Software development methodologies, Scrum for the web, because it allows working through iterations which go in stages of analysis, design, implementation, and testing. Mobile-D in the mobile environment and the modeling language UML for the design of the diagrams, obtaining as a result the systematization and automation in the fact of optimizing the management of processes that was to reduce the time of the consultations, reduce the acquisition of different types of resources, thus avoiding the most common mistakes that the human being can commit, solving favorably and partially the problematic of the estate. In this way, the optimization of processes is concluded, increasing the satisfaction of the owners, specialists and employees of the farm.